O fantástico mundo das fábulas: uma intervenção para o ensino de leitura e escrita - Favorino, Jeane Maria Gomes (2016)
This paper presents a proposal of educational intervention through didactic sequence, which has the object of teaching the mobilization of gender fable, aiming to provide students of the 6th year of elementary school II, with difficulties in literacy, opportunities to develop their competence discursive. The text is based on the studies of Geraldi (2000), Kleiman (2000, 2013), Lajolo (2002), Dezotti (2003), Soares (2005), Jolibert (2008), Dolz and Schneuwly (2010), Koch (2011 , 2015), Passareli (2012), Antunes (2013) Cosson (2014), Marcuschi (2015), Silva (2015), among others, dealing with subjects covered. The sequence used is a proposal of adaptation by Dolz and Schneuwly (2010) Although very old fables continue to attract the attention of many contemporary among others, for the production of more modern texts and / or construction of parodies and paraphrases Classics Esopo and La Fontaine, for example. We defend this text fables as a genre / discourse to be worked in the classroom, as well as being short, they become over time, and allow the various ways to exploit them, which makes students they have fun while learning allowing us a more effective and meaningful practice.